The true north strong and free? Casting shadows on whose history students learn in Canadian universities - Barlow, Amy; Edwards, Fiona (My University, 2021)
Race-based discrimination in Canada exists at the institutional and structural level. While acknowledging its existence is a crucial first step in eradicating this particular form of discrimination, an essential second step includes implementing structural changes at the institutional level in Canadian universities. In an effort to disrupt the Eurocentricity of knowledge production this commentary argues that the Canadian government’s official historical narrative that depicts Canada as being born of the pioneering spirit of British and French white settlers fails to capture the actual history of the country. Rather, it fosters the continuation of the supremacy of whiteness thereby causing significant harm through the perpetuation of racial bias. We argue that the history and contributions of Indigenous, Black, and Chinese Canadians, all of whom were in this country prior to confederation, should be told in a mandatory university course. Our findings indicate that while a number of universities have individual courses, usually electives and some graduate degrees on Indigenous, Black, and Chinese history, there is little offered from the Canadian context and certainly nothing that is a mandatory course requirement. In addition, we suggest compulsory university staff-wide anti-racism training; the ongoing hiring of professors and sessional instructors who are racially representative of the population of Canada; and community outreach, mentorship, and counselling programs that are designed to help students who are underrepresented in Canadian universities. In our opinion, we believe that these changes have the potential to provide a lens to disrupt settler colonial spaces, mobilize race in academic curricula, and encourage social justice actions that can offer a more inclusive learning environment.
Keywords: youth; anti-Black racism; anti-Indigenous racism; anti-Chinese racism; education; Canadian history; university education